SURG-25. LASER INTERSTITIAL THERMAL THERAPY (LITT) FOR INTRACRANIAL LESIONS: A SINGLE- INSTITUTIONAL SERIES, OUTCOMES AND REVIEW OF THE LITERATURE. (11th November 2019) - Dabecco, Rocco; Yu, Alexander; Ranjan, Tulika; Xu, Linda; Aziz, Khaled
Abstract: INTRODUCTION: Laser interstitial thermal therapy (LITT) is a minimally invasive treatment method that provides surgeons with cytoreductive techniques to treat neurosurgical conditions such as primary brain neoplasms, brain metastases, radiation necrosis, and epileptogenic lesions, many of which are located in operative corridors that would be difficult to address via open surgical or are amenable via minimally invasive approaches. Although the use of lasers is not a new concept in neurosurgery, advances in technology have enabled surgeons to perform laser treatment with the aid of real-time MRI thermography as a guide. In this report, we present our institutional series and outcomes of patients treated with LITT for 8 glial neoplasms 12 brain metastases. METHODS: We retrospectively evaluated 20 patients (7 male, 13 female; age range, 28–77 years) who underwent LITT at one or more targets from 2015–2019. RESULTS: In our series, all patients included had prior craniotomy for either primary glioma or metastatic disease. Mean extent of ablation (EOA) was 98% on post-op MRI. Mean progression free survival varied depending on the intracranial pathology, with the glioma cohort (5 months (SDD: 3.51)) demonstrating worse outcomes than metastatic disease (8.2 months (SDD: 4.83)). Only 1 patient experienced immediate post-operative morbidity, 1 patient experienced post-operative mortality secondary to hemorrhage. Mean follow-up was 9.7 months (SDD: 5.35), with one patient lost to follow up immediately post-procedure and excluded from the study. Average hospitalization was 2.4 days (SDD: 1.0). Mean overall survival, post-diagnosis of intracranial lesion, is more favorable for metastatic lesions (48 months (SDD: 27.14)), as compared to primary glial neoplasms (31 months SDD: 11.63)). CONCLUSION: Laser interstitial thermal therapy (LITT) is a safe, minimally invasive treatment method that provides surgeons with cytoreductive techniques to treat neurosurgical conditions. In properly selected patients, this modality offers improved survival outcomes in conjunction with other salvage therapies.